Ursodeoxycholic acid alleviates Xanthium Strumarium induced hepatic and renal toxicity in rats by inhibiting mitochondrial pore opening - Alkac, Zeliha Keskin; Korkak, Fatih Ahmet; Dagoglu, Gurdal; Eroksuz, Yesari; Tanyildizi, Sadettin (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
In Xanthium strumarium toxicity, mitochondrial dysfunction resulting from the opening of mitochondrial pores is identified as the primary mechanism responsible for liver and kidney damage. Ursodeoxycholic acid is known to block mitochondrial pore opening; therefore, this study aims to elucidate the time-dependent therapeutic effect of ursodeoxycholic acid on mitochondrial damage and associated liver and kidney injury in response to X. strumarium exposure. Following the extraction process, Sprague-Dawley rats were administered X. strumarium seed extract (100 gkg-1) via gavage. Ursodeoxycholic acid was administered via oral gavage 6 hours following the administration of the extract, with continued administration over a 7-day period. In conclusion, the toxic effect of X. strumarium was mitigated by ursodeoxycholic acid, which reduced ATP synthase expression, oxidative damage, mitochondrial Ca2+ concentration, and the opening of mitochondrial pores. Ursodeoxycholic acid mitigated the histopathological toxicity induced by X. strumarium, resulting in a reduction in blood glucose, alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, lactate dehydrogenase, blood urea nitrogen, and creatine phosphokinase levels that were closer to control levels. Findings obtained indicate that ursodeoxycholic acid, a blocker of mitochondrial pore opening, can prevent mitochondrial dysfunction and minimize X. strumarium toxicity.
El ácido ursodesoxicólico alivia la toxicidad hepática y renal inducida por Xanthium strumarium en ratas al inhibir la apertura de los poros mitocondriales
Keywords: Xanthium strumarium L.; ursodeoxycholic acid; mPTP; mitochondrial Ca2+; immunohistochemistry